2010
DOI: 10.1128/aem.02249-09
|View full text |Cite
|
Sign up to set email alerts
|

Viral Multiplex Quantitative PCR Assays for Tracking Sources of Fecal Contamination

Abstract: Human and animal fecal pollution of the environment presents a risk to human health because of the presence of pathogenic viruses and bacteria. To distinguish between human and animal sources of pollution, we designed specific real-time reverse transcription (RT)-PCR assays for human and animal enteric viruses, including norovirus genogroups I, II, and III; porcine adenovirus types 3 and 5; ovine adenovirus; atadenovirus; and human adenovirus species C and F, which are excreted by infected humans, pigs, cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(121 citation statements)
references
References 51 publications
4
116
0
1
Order By: Relevance
“…synthesis of cDNA, which was achieved with a High Capacity cDNA Reverse Primer sequences reported by Wolf et al (2010). b Primer sequences reported by Tsai et al (1993).…”
Section: Polymerase Chain Reaction (Pcr) Protocols For the Detection mentioning
confidence: 99%
“…synthesis of cDNA, which was achieved with a High Capacity cDNA Reverse Primer sequences reported by Wolf et al (2010). b Primer sequences reported by Tsai et al (1993).…”
Section: Polymerase Chain Reaction (Pcr) Protocols For the Detection mentioning
confidence: 99%
“…There is also serological evidence for infection by CAV on Brazilian maned wolves (de Almeida Curi et al, 2010). HAdV is ubiquitous in human populations (Eick et al, 2011;Ersching et al, 2010), as well as the virus often being found in environmental samples contaminated by human feces (Miagostovich et al, 2008;Silva et al, 2011;Wolf et al, 2010). HAdV-C has occurred in 14 of the 17 samples (82.35%) and 5 samples were co-infected by CAV (29.41%).…”
Section: Resultsmentioning
confidence: 99%
“…Real-time PCR (qPCR) was applied for the detection human adenovirus (HAdV) genomes using oligonucleotides described previously (VTB2-HAdVCf 5'-AGACGTACTTCAGCCTGAAT-3'; VTB2-HAdVCr 5'-GATGAACCGCAGCGTCAA-3') (Wolf et al, 2010). Nucleotides for the specific amplification of CAV-1 and -2 genomes were originally designed, the forward primer was CAV-F1: 5´-CACGATGTGACCACTGAGAG-3´; reverse: CAV-R1 5´-GGTAGGTATTGTTTGTGACAGC-3´), whose target is a fragment of 300 to 350 base pairs in the gene that encodes the hexon protein.…”
Section: Molecular Detection Of Viral Genomes and Differentiation Of mentioning
confidence: 99%
See 2 more Smart Citations